Contraceptive challenges experienced by women who requested termination of pregnancy services in the Mpumalanga Province - A N Mbokane; V J Ehlers (AOSIS, 2006)
Although contraceptives are available free of charge throughout South Africa, the number of requests for termination of pregnancy (TOP) services continues to increase. Opsomming Alhoewel voorbehoedmiddels gratis dwarsdeur Suid-Afrika beskikbaar is, word die aanvraag vir dienste vir die beeïndiging van swangerskap al groter. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.